New system of conditionality in the European Union law - Gontarski, Waldemar (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The new regime of conditionality relating to the protection of the rule of law, postulated in the conclusions of the European Council and proposed in the Commission’s proposal, does not meet the dictionary requirements of genuine conditionality in two ways. Firstly, it does not introduce clear criteria as to the rule of law. Secondly, the rule of law is not required to be linked – on a sufficiently direct causal nexus – with what is to be dependent on the “rule of law”, i.e. the rule of law is not required to be sufficiently directly related in an actual (and not just potential) manner to certain (specific) EU finances, although the stated aim is to protect the financial interests of the Union. In such circumstances, the principle of legal certainty, being one of the elements of the actual rule of law, is breached. Moreover, the new conditionality duplicates and modifies to a certain extent the treaty procedure for the protection of the rule of law, what in itself constitutes a breach of treaty law by circumventing the law if only because the treaty procedure is more difficult to start than the one under the new conditionality system due to the required majority in the Council and unanimity in the European Council.